2019
DOI: 10.3762/bjnano.10.87
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, ultraviolet-induced, reversibly switchable wettability of superhydrophobic/superhydrophilic surfaces

Abstract: Controllable wettability is important for a wide range of applications, including intelligent switching, self-cleaning and oil/water separation. In this work, rapid switching and extreme wettability changes upon ultraviolet (UV) illumination were investigated. TiO2 nanoparticles were modified in solutions of trimethoxy(alkyl)silane, and the suspensions were sprayed on glass substrates. For such samples, the water contact angle (WCA) was shown to transition from a superhydrophobic (WCA ≈ 165°) to a superhydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The inorganic semiconductor oxide materials with optical triggering-yielded electron-hole pairs usually are used to regulate the reversible light-responsive wettability, such as titanium dioxide (TiO 2 ), zinc oxide (ZnO), tin dioxide (SnO 2 ), tungsten trioxide (WO 3 ) and vanadium oxide (V 2 O 5 ) etc [29,55,56] . In the preparation of wettability-regulating superwettability surfaces, photosensitive inorganic semiconductor materials mainly utilize the free conversion of oxygen vacancies and hydroxyl groups under ultraviolet (UV) light irradiation and dark treatment (or heat treatment) to change the surface chemical polarity, thereby achieving the switchable wettability.…”
Section: Lightmentioning
confidence: 99%
“…The inorganic semiconductor oxide materials with optical triggering-yielded electron-hole pairs usually are used to regulate the reversible light-responsive wettability, such as titanium dioxide (TiO 2 ), zinc oxide (ZnO), tin dioxide (SnO 2 ), tungsten trioxide (WO 3 ) and vanadium oxide (V 2 O 5 ) etc [29,55,56] . In the preparation of wettability-regulating superwettability surfaces, photosensitive inorganic semiconductor materials mainly utilize the free conversion of oxygen vacancies and hydroxyl groups under ultraviolet (UV) light irradiation and dark treatment (or heat treatment) to change the surface chemical polarity, thereby achieving the switchable wettability.…”
Section: Lightmentioning
confidence: 99%
“…TiO 2 nanostructures have been grown on three-dimensional reduced graphene oxide porous structures and play an important role. Pan et al [71] reported a TiO 2 nanoparticle (NP) coating modified with 1H,1H,2H,2Hperfluorooctyl(trimethoxy)silane. The CAs could rapidly change from 165 • to 0 • in 10 min after heating.…”
Section: Controllable Wettabilitymentioning
confidence: 99%
“…Natural surfaces represented by the lotus leaf surface show superhydrophobic in air, and fish scales show superoleophobicity in water, having already disclosed an important role of the cooperation of surface chemical components and roughness on multiple scales. , Inspired by these marvelous natural materials, various surfaces with special superwettabilities have been developed. Most solid substrates exhibit irreversible wetting behaviors, for comparison, smart materials showing switchable superwetting properties are more desirable, as their surface wettability can be modulated by changing the surface chemistry via the employment of stimuli-responsive polymers, smart modifiers, and inorganic semiconductors or by external stimuli including pH, light, temperature, and electricity. …”
Section: Introductionmentioning
confidence: 99%